National Study of Firearm Presence and Storage Practices in Homes of Rural Adolescents - Benjamin Linden; Megan Sinik; Kristel Wetjen; Pam Hoogerwerf; Junlin Liao; Charles Jennissen (Western Journal of Emergency Medicine)
Introduction: Firearm-related unintentional and suicide death rates in adolescents are higher in rural areas. In 2020, the overall rural firearm death rate was 28% higher than the urban rate. Firearm access significantly increases the risk. The study objective was to evaluate firearm exposure and storage practices in the homes of rural adolescents. Methods: We conducted a cross-sectional, anonymous survey of attendees at the 2021 National FFA (formerly Future Farmers of America) Convention & Exposition. Descriptive, bivariate, and multivariable logistic regression analyses were performed. Results: A total of 3,296 adolescents 13–18 years of age participated in our survey. Overall, 87% of respondents reported having rifles/shotguns, 71% had handguns, and 69% had both rifles/shotguns and handguns in their homes. The odds of those living on farms having rifles/shotguns and handguns were 7.5 and 2 times higher, respectively, as compared to those from towns. Rifles/shotguns and handguns were stored unlocked and/or loaded at least some of the time in 63% and 64% of homes, respectively. Respondents from farms had 1.5 and 1.7 times greater odds of having rifles/shotguns and handguns stored unlocked and loaded, respectively, as compared to those from town. The South, West and Midwest had odds that were 5.9, 3.2, and 2.8 times higher for rifles/shotguns and 8.1, 5.2, and 4.3 times greater for handguns to be stored loaded and unlocked, respectively, as compared to the Northeast. Only 43% of respondents reported ammunition being locked and stored separately from firearms. Conclusion: Most rural adolescents surveyed lived in homes with firearms, and a large proportion of those firearms were not stored safely. Firearm presence and storage differed by region and home setting. Unsafe storage practices could be contributing to the higher unintentional and suicide death rates seen in rural areas.